2022
DOI: 10.1007/s13679-022-00488-8
|View full text |Cite
|
Sign up to set email alerts
|

Criterion-Related Validity of Field-Based Methods and Equations for Body Composition Estimation in Adults: A Systematic Review

Abstract: Purpose of Review Overweight and obesity are associated to health prognosis. Therefore, body composition assessment is an important health outcome, especially in adult population. We analyzed the criterion-related validity of existing field-based methods and equations for body composition estimation in adults aged 19–64 years. Recent Findings One hundred studies met inclusion criteria. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Body composition methodology and technologies vary in accuracy and applications. The two methods selected, CBE and BIA, for investigation in this study have similar ranges of accuracy as reported in the literature [15,27].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Body composition methodology and technologies vary in accuracy and applications. The two methods selected, CBE and BIA, for investigation in this study have similar ranges of accuracy as reported in the literature [15,27].…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, potential limitations to BIA's utility for some assessment settings is inability to ensure that those being measured have a normal hydration status and reliability of measurement across sex, race, and ethnicity in a large population [14]. Circumference-based equations (CBE) are a clinically accepted assessment technique to estimate percent body fat (%BF), and are widely used because of their minimal footprint, low-cost, and time efficient [15].…”
Section: Introductionmentioning
confidence: 99%
“…[48]. Furthermore, prediction equations for adult body composition have been demonstrated to provide accurate results, minimizing prediction errors when compared with “gold‐standard” methods [49].…”
Section: Discussionmentioning
confidence: 99%
“…Although technological advances have allowed the creation of more precise instruments such as magnetic resonance imaging or dual-energy X-ray absorptiometry, [15,16] anthropometric measures and health indices are widely used, mainly due to their low cost, simple application, and validity for estimating body size. [17,18] In this context, government authorities in Chile have developed manuals that incorporate anthropometric indicators and the calculation of health indices to monitor the comprehensive health of children and adolescents. [19][20][21] Specifically, they are included for the diagnosis and follow-up of PA interventions aimed at preventing or treating overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Although technological advances have allowed the creation of more precise instruments such as magnetic resonance imaging or dual-energy X-ray absorptiometry, [15,16] anthropometric measures and health indices are widely used, mainly due to their low cost, simple application, and validity for estimating body size. [17,18]…”
Section: Introductionmentioning
confidence: 99%